Black Hills - Roberts, Nora. (New York : G.P. Putnam's Sons, 2009)
In the rugged Black Hills of South Dakota, a childhood friendship matures into an adult passion when something ... or someone ... threatens Lil Chance and her dream to open a wildlife refuge. The heartless killing of Lil's beloved cougar and recollections of an unsolved murder catapult New York investigator Coop Sullivan into action to keep Lil safe.
Keywords: Animal sanctuaries -- Fiction; Black Hills (S.D. and Wyo.) -- Fiction; Romantic suspense fiction